56. Low-dose protocol for computed tomography angiography of thoracic aorta with ASiR-V iterative reconstruction. (December 2018) - Origgi, D.; Budascu, D.; Consiglio, E.; Marco, P. De; Emiro, F.; Annoni, A.
Abstract : Purpose: To assess the feasibility of a Computed Tomography Angiography (CTA) protocol with low kVp and the new iterative reconstruction (IR) algorithm ASiR-V. Methods: 63 patients (43 men and 20 women) were scanned on a 256 slices CT Revolution in prospective axial mode, with 80 kVp and mA ranging from 350 to 600 depending on patient BMI. Images were reconstructed with Filtered Back-projection (FBP) and with ASiR-V ranging from 20% to 100%. Images were analyzed quantitatively, placing ROIs in the ascending aorta, aortic arch and descending aorta to evaluate noise, signal-to-noise (SNR) and contrast-to-noise (CNR) ratio for all patients and for all levels of ASiR-V. Qualitative image evaluation was performed by two radiologist (both >10 years of experience) using the LIKERT scale. For all patients effective dose (E) is calculated from DLP. In addition, a comparison with the former clinical protocol on a CT Discovery with ASiR instead of ASiR-V was performed. Results: Passing from FBP to ASiR-V 100%, noise is reduced on average up to 31%, while SNR and CNR are improved on average up to 46%. Subjective analysis gives the highest LIKERT score to the images reconstructed with ASiR-V 60% (3.8 ± 0.3 for reader 1, 3.8 ± 0.6 for reader 2–k = 0.87). With this IR level, noise is reduced by 20%, while SNR and CNR are improved by 25%. In a subpopulation with BMI >30, ASiR-V 80% resulted in the best compromise between dose reduction and image quality. Considering the same 50% IR level for ASiR and ASiR-V, with ASiR-V we observe noise reduction (10–27%), CNR (12–40%) and SNR(6–32%) improvement, while dose decreases form 1.5 to 1 mSv. Conclusions: The new proposed protocol at 80 kVp tube voltage and 60% ASiR-V allows high image quality and mean doses of only 1 mSv.